Factors that affecting financial management behaviour among the youth: a case study in Kajang, Selangor / Muhammad Izzuddin Md Rosnan - Md Rosnan, Muhammad Izzuddin (Faculty of Business and Management, 2019)
This research is conduct to analyse the factors that affecting the financial management behaviour among youth in Kajang, Selangor. From the prior research shows there are many factors that can affect to the financial management behaviour. Aims for this study is to identify the significant relationship between dependent variable and independent variables by using empirical analysis which are test on the self-administered or questionnaire that has been distributed. Financial Management behaviour is choose the dependent variable and there are four independent variable selected that is financial knowledge, financial attitude, locus of control and bank policies. The significant of this research will give knowledge and acknowledge the youth and the future generation on how to have a proper manage of finance. The data from the answered questionnaire been conducted using Statistical Package of Social Science Version 22 (SPSS) to get the analysis. Cronbach's Alpha for this research for every variable is in good and excellent reliability. The findings have shown that all these four independent variables have explained Only 22% of the variance of financial management behaviour. Positive relationship is shown for all these four variable even locus of control and bank policies is not significant. Two of the variables are show not significant that are financial knowledge and financial attitude and the other two are not significant.